Metabolic energy expenditure during level, uphill, and downhill running - Looney, D. P.; Hoogkamer, W.; Kram, R. (European Journal of Applied Physiology, 2025)
Purpose To extend the Running Energy Expenditure Estimation (RE3) model for predicting metabolic rates during uphill and downhill running as well as to enhance the Hoogkamer-Taboga-Kram (HTK) equation for estimating metabolic rates during level and uphill running.